Խաղտիք- Համշենը Հայոց բնօրրանի և պետականության մաս - Սահակյան, Լուսինե
Հոդվածում մանամասնորեն ներկայացվում է Մեծ Հայքի հյուսիս-արևմուտքում՝ Տայքի նահանգին սահմանակից Պարխարյան լեռնահովիտներում սփռված Խաղտիքի երկրամասը, որ դեռևս վաղնջական ժամանակներից եղել է հայոց բնօրրաններից մեկը։ Խաղտիքում հայ ժողովուրդը կերտել է իր ռազմաքաղաքական, հոգևոր և մշակութային պատմությունը, որը պետք է հող նախապատրաստեր հետագայում այնտեղ Համշենի հայկական իշխանության կազմավորման համար։ Расположенная на северо-западе Мец Айка (Великой Армении) провинция Хахтик с древнейших времен упоминается как прародина арменохалибов – армян хахтикцев. Местность эта была известна своими железными рудниками. Коренные жители в основном занимались обработкой железа, чем и обусловлено их наименование – халюб, или халиб, являющееся не этнонимом, а названием их профессиональной деятельности. Из-за богатых рудников этот район Пархарских гор стал постоянной мишенью для чужеземных захватчиков. В IV в. он отмечается как 16-я область Мец Айка, в V в. – часть провинции Тайк в составе области Арсяц пор. Рассматриваемые факты ведут корни Мамиконянов в страну Хахтик, и их происхождение следует искать на северо-западе Армянского нагорья․ С древнейших времен до VIII века Хахтик вместе с Тайком являлись княжеским владением Мамиконянов. Не случайно неприступный Хахтик в V веке становится убежищем для армянских нахараров. Сопоставление свидетельств Лазара Парбеци и амшенских писцов ХVI века подводит нас к выводу, что Хахтик был также священным местом: в селе Егновит образованного впоследствии на этой территории княжества Амшена были преданы земле останки мучеников Вардананц – Амаяка Мамиконяна и его соратников. Таким образом, провинцию Хахтик следует рассматривать как неотъемлемую часть Мец Айка. Происходившие здесь военно-политические, духовные и культурные события подготовили почву для основания здесь в ХVIII веке армянского княжества Амшена, ставшего одним из духовных центров армян и армянской письменности. The Region of Khaghtiq, located in the north-west of Metz Hayq (Greater Armenia), had been mentioned from ancient times as the ancestral homeland of armenokhalibs, or Khaghtiq Armenians. The terrain was known for its iron mines. The aboriginal people were mainly engaged in processing iron ore, which is why they were called khalyub or khalilb – which word is not an ethnonym, but denotation of their professional occupation. For the abundance of iron ore on the slopes of the Parkhar mountains, this area had turned into a perpetual target for foreign invaders. In the IV century it was mentioned as the 16th district of Metz Hayq, and later, in the V century it was incorporated in the Taiq Region as part of the Province of Arsyats Por. The facts studied lead the Mamikonyans’ roots toward the land of Khaghtiq, and their origination should be sought in the north-west of the Armenian Highlands. From ancient times until the VIII century, Khaghtiq with Taiq were the princely fiefdom of the Mamikonyans. It is not coincidental that the inaccessible region of Khaghtiq served as a refuge for Armenian nobles. Having juxtaposed the evidence by Ghazar Parpetsi and the XVI century scribes of Hamshen, we arrive at the conclusion that Khaghtiq was also a sacred place: in the village of Yeghnovit of the Principality of Hamshen, formed subsequently on this territory, the remains of the Vardanants martyrs – Hmayak Mamikonyan and his comrades-in-arms – were interred. Thus, the Region of Khaghtiq should be viewed as an inalienable part of Metz Hayq. The military, political, spiritual and cultural events there had paved the way for founding the Armenian Principality of Hamshen in the XVIII century, which was to become one of the spiritual centers of Armenians and Armenian writing.
Keywords: Հայոց պատմություն